2020
DOI: 10.3390/genes11101116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs Controlling α-Glucosidase Inhibitory Activity in Pepper (Capsicum annuum L.) Leaf and Fruit Using Genotyping-by-Sequencing Analysis

Abstract: Diabetes mellitus, a group of metabolic disorders characterized by hyperglycemia, is one of the most serious and common diseases around the world and is associated with major complications such as diabetic neuropathy, retinopathy, and cardiovascular diseases. A widely used treatment for non-insulin-dependent diabetes is α-glucosidase inhibitors (AGIs) such as acarbose, which hinders hydrolytic cleavage of disaccharides and retard glucose absorption. The ability to inhibit α-glucosidase activity has been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This result agrees with previous studies on pepper and other plant samples. Pepper leaves harvested at different stages i.e., April, July, and October were found to show an average of 36.18%, 66.61%, and 47.29% AGI activities, respectively [66]. Similarly, Kim et al reported that leaves extracts of pepper exhibited 61.1% α-glucosidase inhibition [24].…”
Section: Relationship Between Agi Activity and Metabolite Profile Of Pepper Leaves 231 Evaluation Of Agi Activity Of The Pepper Leaf Extrmentioning
confidence: 96%
“…This result agrees with previous studies on pepper and other plant samples. Pepper leaves harvested at different stages i.e., April, July, and October were found to show an average of 36.18%, 66.61%, and 47.29% AGI activities, respectively [66]. Similarly, Kim et al reported that leaves extracts of pepper exhibited 61.1% α-glucosidase inhibition [24].…”
Section: Relationship Between Agi Activity and Metabolite Profile Of Pepper Leaves 231 Evaluation Of Agi Activity Of The Pepper Leaf Extrmentioning
confidence: 96%
“…In recent years, in addition to different sugar-based inhibitory molecules being designed (24), extracts obtained from different parts of various plants have also been reported to exhibit inhibitory activity against glucosidase (25)(26)(27). Most of the ɑglucosidase inhibitors in these plants are secondary metabolites such as alkaloids, phenolic acids, flavonoids, terpenoids, anthocyanins, and their glycosides, and these have been suggested to have much stronger inhibitory potentials than the inhibitory effect obtained from acarbose (28).…”
Section: According Tomentioning
confidence: 99%
“…Moreover, 15 eQTLs for flavonoid pathway genes were identified: (i) eQTLs for CHS-1, CHS-2, CHI-2 and FLS co-localized on P01 and overlapped with a mQTL for naringenin chalcone, eQTLs for CHS-1, CHS-2, CHI-1, CHI-2 and FS-2 colocalized with a naringenin chalcone mQTL on P09, (iii) eQTLs for F3'H-1 and F3'H-4, and F3H were detected on P03, P04 and P08, respectively (Wahyuni et al, 2014) (Table 1; Supplementary Data S2). In a study aimed at identifying QTLs associated with aglucosidase inhibitory activity of flavonoids and other compounds present in pepper leaves and fruits (Park et al, 2020), the authors found a QTL on chromosome 9, which co-located with the cluster of mQTLs and eQTLs identified by Wahyuni et al (2014). In a recent work, Wu et al ( 2022) used a F 2 population, resulting from the cross between the flavonoid-contrasting C. annuum accessions Long Sweet (P12) and AC2212 (P24), to identify a major QTL (fc5.1) controlling the accumulation of chalcones, flavonols and flavones located at 228 Mbp on pepper chromosome 5.…”
Section: Eggplantmentioning
confidence: 99%